2008
DOI: 10.1091/mbc.e07-11-1173
|View full text |Cite
|
Sign up to set email alerts
|

Gcn4 Is Required for the Response to Peroxide Stress in the Yeast Saccharomyces cerevisiae

Abstract: An oxidative stress occurs when reactive oxygen species overwhelm the cellular antioxidant defenses. We have examined the regulation of protein synthesis in Saccharomyces cerevisiae in response to oxidative stress induced by exposure to hydroperoxides (hydrogen peroxide, and cumene hydroperoxide), a thiol oxidant (diamide), and a heavy metal (cadmium). Examination of translational activity indicates that these oxidants inhibit translation at the initiation and postinitiation phases. Inhibition of translation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 57 publications
2
89
0
Order By: Relevance
“…Decreased TOR-signaling activities have been shown to enhance Gcn4 (a nutrient-and stresssensing transcription factor) expression, which activates genes involved in nitrogen utilization (Valenzuela et al 2001). Gcn4 was also required for the response and resistance to hydrogen peroxide (Mascarenhas et al 2008). Figure 3E showed that gcn4D specifically abolished bmh1D-and tor1D-induced but not CR-induced heat resistance.…”
Section: Resultsmentioning
confidence: 97%
“…Decreased TOR-signaling activities have been shown to enhance Gcn4 (a nutrient-and stresssensing transcription factor) expression, which activates genes involved in nitrogen utilization (Valenzuela et al 2001). Gcn4 was also required for the response and resistance to hydrogen peroxide (Mascarenhas et al 2008). Figure 3E showed that gcn4D specifically abolished bmh1D-and tor1D-induced but not CR-induced heat resistance.…”
Section: Resultsmentioning
confidence: 97%
“…As shown in S. cerevisiae this post-translational event occurs at the onset of the stress response in a Gcn2/Ppk28-dependent manner (Mascarenhas et al, 2008). Another eIF2a kinase, Hri2, becomes also critical for survival upon long exposure of fission yeast cells to stress (Dunand-Sauthier et al, 2005;Zhan et al, 2002).…”
Section: The Sty1 Regulatory Signals On Translationmentioning
confidence: 88%
“…The 4E-BPs play nonredundant roles in the adaptive growth response to nitrogen limitation as deletion mutants prevent pseudohyphal development and invasive growth of the S1278b strain (Ibrahimo et al 2006), while S288c deletion strains are sensitive to growth on alternative nitrogen sources (Cridge et al 2010). Translational repression upon cell treatment with the antipsychotic drug chlorpromazine or the oxidants cadmium and diamide are partially dependent upon Eap1 (Deloche et al 2004;Mascarenhas et al 2008), while caf20D displays synthetic growth phenotypes when combined with tif3D (eIF4B deletion) (de la Cruz et al 1997) or the tif4631-459 allele that disrupts eIF4G1 binding to eIF4E (Hershey et al 1999). These phenotypes are consistent with both 4E-BPs being translational repressors.…”
Section: Regulating Eif4e-eif4g Interactions By 4e-bpsmentioning
confidence: 99%